Empowering Kelon (Oncology Class) in Screening and Early Detection of Breast Cancer in The South Pekalongan Health Centre Working Area - Isrofah Isrofah; Dani Prastiwi; Rr. Vita Nurlatif; Irene Dwitasari Wulandari (Universitas Muhammadiyah Malang, 2025)
Breast cancer has the highest incidence of all cancers in Indonesia. Breast cancer is a type of cancer that often occurs in women, especially in women who are close to 50 years old. Breast cancer in Indonesia is often found in an advanced stage and is already difficult to treat. Efforts can be made to reduce the incidence of advanced breast cancer by conducting routine breast examinations. Early screening measures need to be done to detect abnormal cells before they develop into deadly cancer. With these examinations carried out regularly, the discovery or screening and early detection can reduce the incidence of advanced breast cancer. The aim of this activity is to increase the knowledge and skills of the health cadres so that they can become proficient in conducting the BSE examination. Furthermore, cadres are also expected to be able to teach other women of childbearing age in the area where they live. This activity was carried out at the South Pekalongan Health Center, which was attended by 34 cadres of Posbindu South Pekalongan Health Center in the form of counseling with lecture and question and answer methods and demonstrations on Breast Self Examination (BSE). Pretest and Postest were conducted to measure cadres' knowledge before and after education. The results of this level of service can increase the knowledge of respondents, which initially the majority of respondents' knowledge level in the poor category was 66% in the poor category and after being given education the level of knowledge became 90% in the very good category. Similar activities are needed for coaching posyandu cadres to have health maintenance skills, especially screening and early detection of breast cancer. Of course, support and participation from residents and village officials are needed.